Singapore's Changing Demography, the Eldercare Predicament and Transnational 'Care' Migration. Issue 2 (26th June 2014) - Yeoh, Brenda S.A.; Huang, Shirlena
Abstract Scholars have recently argued that globalisation processes have significantly altered not just the productive but reproductive sphere. 'Reproduction' is formulated to include both biological and social reproduction, and which at the individual level requires 'care' throughout the life-cycle – that is, from cradle to grave – in sustaining the body in its corporeal and affective aspects. Concepts that have emerged in the literature in recent decades such as the 'transnational family', 'global householding' and 'global care chain' draw attention to the observation that the formation and sustenance of households is increasingly reliant on the international movement of people and transactions among household members residing in more than one national territory. Applying these notions to the context of the city-state of Singapore where the predicament around eldercare (resulting essentially from rapid fertility decline, shortages of Singapore women's reproductive labour and rigidities in the gender household division of labour) accompanies rapid globalisation, this paper examines strategies of care substitution which draw on the lowly paid labour of two groups of transnational subjects (mainly women) – transnational domestic workers working in the privatised sphere of the home, and transnational healthcare workers in institutionalised settings. The paper reflects upon the interdependencies between flows of transnational care migration and delves into the gender and class implications of these flows for an understanding of the links between transnational migration and social change.